Analysis of Inner Conflict and Social Facts in the Novel Layangan Putus by Mommy Asf: A Psychological Study of Abraham Maslow’s Literature - Aini, Isna Nor; Fathurohman, Irfai; Darmuki, Agus (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
Inner conflict and social facts are forms of social dynamics in social life. Abraham Maslow conceptualized humanism as the resolution of inner conflicts and social facts. This study aims to describe (1) the cause of the inner conflict of the main character Kinan in the Mommy Asf Layangan Putus novel, (2) social facts in the kite breaking novel, and (3) the resolution of inner conflicts and social facts with Abraham Maslow's humanistic theory. This research method is descriptive qualitative with a psychological approach to the literature of Abraham Maslow. The research data is in the form of quotes from inner conflict and social facts about the main character. The data source is obtained from the novel Layangan Putus by Mommy Asf. Data analysis refers to the Miles Huberman model through data reduction activities, data presentation, and retraction conclusions. The results obtained from this study consist of (1) two forms of conflict, namely: (a) physical conflict with two forms; verbal disputes and violence. (b) inner conflict in two forms; self-resistance and fear; (2) three forms of social facts, namely: (a) external with two markers; pilgrimage and natural beauty; (b) determined coercive with one marker, namely; persuade according to the vision; (c) general with two markers; writing community and da'wah community; (3) five forms of problem solving, namely physiological needs; security needs; the need for affection; the need for appreciation; and self-actualization needs. The measures of the success of the conflict in the Kite Putus novel are injustice, communication, and cooperation.